EFEKTIVITAS METODE APLIKASI VIDEO INOVATIF DENGAN METODE DEMONTRASI MENYIKAT GIGI TERHADAP KEBERSIHAN GIGI DAN MULUT SISWA SEKOLAH DASAR INPRES BUNTONG KECAMATAN MANDOLANG KABUPATEN MINAHASA - I Ketut Harapan; Jean Z. Adam (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2020)
ABSTRACTDental and oral health in Indonesia still needs special attention from dental and mouth health personnel. This is because most people in Indonesia ignore their own oral health, including elementary school age children. Primary school age group is a group that is susceptible to dental and oral diseases so it needs to be considered and prevented properly. As many as 25.2% of children aged 10-14 years who have dental and mouth problems in Indonesia. This condition can affect the degree of their health in the process of growth and even their future. School Dental Health Business (UKGS) is a public health business aimed at school communities, namely students, teachers and other school employees to get more attention.The research method used in this study is a quasi experimental design with one group pre post test design on the treatment of group A and group B. How to take a sample that is using purposive sampling with incusive criteria, the number of samples during the study 60 respondents class IV and V The instrument in this study used a questionnaire measuring knowledge and the OHIS examination format measuring dental hygiene. The results showed that the results of the Mann-Whitney Test obtained Asymp.Sig (2 tailed) 0.002 probability value 0.005 thus there was a significant difference with the Mean value in the innovative video group 39.9 Mean value of the demonstration group 21.1 on the index OHIS. And the Mean value of the knowledge level in the video group 37.5 Mean value in the demonstration group 23.5. It can be concluded that the innovative video application method is more effective than the demonstration method for improving dental and oral health status of students. reduce consuming foods that contain sugar.